2014
DOI: 10.1117/1.jbo.19.8.086002
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of interaction of low-frequency electric field with biological tissues upon optical clearing with optical coherence tomography

Abstract: The influence of a low-frequency electric field applied to soft biological tissues ex vivo at normal conditions and upon the topical application of optical clearing agents has been studied by optical coherence tomography (OCT). The electro-kinetic response of tissues has been observed and quantitatively evaluated by the double correlation OCT approach, utilizing consistent application of an adaptive Wiener filtering and Fourier domain correlation algorithm. The results show that fluctuations, induced by the el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 22 publications
(24 reference statements)
0
7
0
Order By: Relevance
“…The imaging principle of OCT indicates that it has the capacity to image the tissue within 1 to 3 mm depth in vivo, 37-39 which makes it a powerful tool to assess the optical clearing process in tissues. 22,23,40 In this study, we used a commercial OCT system (OCP930SR, Thorlab Inc., Newton, New Jersey) working at ð930 AE 5Þ nm with ð100 AE 5Þ nm full-width-half-maximum, with an optical power of 2 mW, a maximum image depth of 1.6 mm, an axial resolution of 6.2 μm (in air), and a lateral resolution about 10 μm. The saturated sucrose (78.9%) or saturated fructose (67.1%) induced skin optical clearing efficacy was assessed quantitatively by analyzing the improvements in imaging depth and signal intensity at the given depth.…”
Section: Optical Coherence Tomography For Assessingmentioning
confidence: 99%
“…The imaging principle of OCT indicates that it has the capacity to image the tissue within 1 to 3 mm depth in vivo, 37-39 which makes it a powerful tool to assess the optical clearing process in tissues. 22,23,40 In this study, we used a commercial OCT system (OCP930SR, Thorlab Inc., Newton, New Jersey) working at ð930 AE 5Þ nm with ð100 AE 5Þ nm full-width-half-maximum, with an optical power of 2 mW, a maximum image depth of 1.6 mm, an axial resolution of 6.2 μm (in air), and a lateral resolution about 10 μm. The saturated sucrose (78.9%) or saturated fructose (67.1%) induced skin optical clearing efficacy was assessed quantitatively by analyzing the improvements in imaging depth and signal intensity at the given depth.…”
Section: Optical Coherence Tomography For Assessingmentioning
confidence: 99%
“…An OCT angiography (Angio‐OCT) was applied to monitor in vivo skin optical clearing efficacy to obtain the quantitative comparisons, including imaging performances optimization, changes of skin optical properties and RI mismatching extent, and permeability rate as well. The Angio‐OCT used here not only has the capacity to produce high‐resolution 3‐dimention (3‐D) images of the in vivo tissues in different depth noninvasively completely with labelling free , but also can obtain the blood flow distribution information additionally .…”
Section: Introductionmentioning
confidence: 99%
“…3,4 In a previous study, we found a mixture of fructose with PEG-400 and thiazone (FPT) allows in vivo blood flow imaging with higher contrast and resolution. 16 Currently, evaluation of a newly developed OCA is usually performed by imaging the blood flow in vivo 5,16 or by measuring the optical properties via integration sphere, 17 diffuse reflectance spectroscopy, 18 and OCT 7,[19][20][21] separately. LSCI allows a fullfield imaging of the cutaneous blood flow using speckle dynamics and has been used for evaluating the OCA-induced improvement in both the contrast and resolution of blood flow imaging.…”
Section: Introductionmentioning
confidence: 99%
“…7,19,21,26 The depth-resolved OCT signal offers an approach for measuring optical properties. 7,[19][20][21] Thus, the attenuation coefficient, refractive-index mismatching extent, and permeation rate of different tissue compounds can be quantified, which has played a vital role in evaluating the changes of tissue optical properties in previous studies. 21 OCA processing, skin optical properties, and blood flow imaging performances are closely correlated, but their relationship has seldom been reported.…”
Section: Introductionmentioning
confidence: 99%